Design And Investigation On Wideband Antenna Based On Polydimethylsiloxane (PDMS) For Medical Imaging Application - Nga, Yan Li; Zakaria, Zahriladha; Shairi, Noor Azwan; Alsariera, Hussein Salameh Mahmoud; Al-Ahnomi, Rammah Ali Hussien (WYDAWNICTWO SIGMA-NOT, 2020)
This paper presents an antenna for the medical imaging application which can detect unusual tissues on any part of the body. A compact design of wideband antenna with wearable properties is proposed for the medical imaging application. The wideband antenna is designed with introducing notches to the patch and a t-shaped slot at the partial ground. Polydimethylsiloxane (PDMS) is introduced to the antenna for the implementation of the wearable antenna. The proposed antenna operated in a frequency range of 3GHz to 6GHz. The antenna that embedded with PDMS shows a good agreement to the antenna without PDMS. An experimental proposed structure shows a good agreement with the simulated results. The overall dimension of the antenna is 24mm(W) x 38mm( L) which consider is a miniature antenna. This proposed design give an alternative solution for the antenna which cannot be wear on the body and protect the antenna. The introduction of PDMS will reduce the signal reflection cause by the high coupling of the human body.